?-III-spectrin spinocerebellar ataxia type 5 mutation reveals a dominant cytoskeletal mechanism that underlies dendritic arborization. - Avery, A.W.; Thomas, D.D.; Hays, T.S. (Proceedings of the National Academy of Sciences of the United States of America, 2017)
A spinocerebellar ataxia type 5 (SCA5) L253P mutation in the actin-binding domain (ABD) of ?-III-spectrin causes high-affinity actin binding and decreased thermal stability in vitro. Here we show in mammalian cells, at physiological temperature, that the mutant ABD retains high-affinity actin binding. Significantly, we provide evidence that the mutation alters the mobility and recruitment of ?-III-spectrin in mammalian cells, pointing to a potential disease mechanism. To explore this mechanism, we developed a Drosophila SCA5 model in which an equivalent mutant Drosophila ?-spectrin is expressed in neurons that extend complex dendritic arbors, such as Purkinje cells, targeted in SCA5 pathogenesis. The mutation causes a proximal shift in arborization coincident with decreased ?-spectrin localization in distal dendrites. We show that SCA5 ?-spectrin dominantly mislocalizes ?-spectrin and ankyrin-2, components of the endogenous spectrin cytoskeleton. Our data suggest that high-affinity actin binding by SCA5 ?-spectrin interferes with spectrin-actin cytoskeleton dynamics, leading to a loss of a cytoskeletal mechanism in distal dendrites required for dendrite stabilization and arbor outgrowth.